SUSCEPTIBILITY TESTS OF ANOPHELES STEPHENSI WITH SOME CHLORINE, PHOSPHORUS, CARBAMATE AND PYRETILROID INSECTICICDES IN SOUTH OF IRAN - M.Iranpour; M.R. Yaghoobj-Ershadi; M. Motabar (Tehran University of Medical Sciences, 1993)
Susceptibility tests were carried out on Anopheles stephensi with D.D.T(4%), dieldrin (4%), malathion(5%), propoxus (0.1%), primphos-methyl (O.lmg/cm2), lambda-cyhalothrin (0.1%), permethrin (0.25%) and deltamethrin (0.025%) during 1990-94 in Minab county, soutern Iran, using W.H.O standard method. Results showed that An. stephensi was susceptible to malathion, propoxur, primphos - methyl, lambda- cyhalothrin permethrin and deltamethrin, also LT5O was 5,19.5, less than 1.less than 1,3 and less than 1 minute, respectively. Results indicated that An.stephensi was still resistant to D.D.T and dieldrin but susceptibility level has increased. Mortality rate was 36.1 and 80.6 when the species was exposed to D.D.T and dieldrin impregnated papers for 60 minutes, respectively.